La Chimica a Palermo tra le due guerre - Maggio, Antonella Maria; Zingales, Roberto (Chimica nella Scuola, 2022)
After Cannizzaro and Paternò’s departure, Chemistry in Palermo lost its cultural leadership in Italy, whilst some feeble attempts were being made to create a modern chemical industry, to exploit local resources. In the academic field, a new chemical element was identified. In the industrial field, despite the autarkic support of the government, the inability to keep up with the market’s requests, the inadequacy of the industrial organisation and the negative influence it received from politics, led even promising industrial enterprises to failure.